Attention to acute cerebrovascular disease in Guipúzcoa: description of the results of a reference hospital in a centralized care model - G. Fernández-Eulate; P. Arocena; A. Muñoz-Lopetegi; J. Rodriguez-Antigüedad; D. Campo-Caballero; J. Equiza; N. Andrés; A. de Arce; F. Gonzalez; N. Diez; J. Basterrechea; E. Suquia; et al. (Neurología (English Edition), 2022)
Introduction: In the last 15 years, considerable improvements have been made in acute stroke care in Guipuzkoa, including the implementation of a centralised care model at Hospital Universitario Donostia (HUD), improved coordination between professionals, early detection campaigns, new treatments, a stroke unit, and specific rehabilitation. The aim of this work is to describe the results of a reference hospital (HUD) in a centralised care model. Material and methods: We performed a retrospective observational study of a sample of patients discharged between August and December 2015 from the HUD with a diagnosis of acute stroke (ICD-9-CM codes 430-436, except 433.10). We review patients’ baseline characteristics, acute-phase care, and functional outcomes and mortality at discharge and at one year. Results and discussion: We identified 536 patients, with a mean age of 73.6 years and a high comorbidity rate. Ischaemic stroke accounted for 64.8% of patients, followed by haemorrhagic stroke (20%) and transient ischaemic attack (14.8%). A total of 53% of patients were attended in < 6 hours, with code stroke being activated in 37.1%; 52.2% of patients were admitted to the stroke unit. Intravenous therapy was administered to 8.3% of patients with ischaemic stroke, and 9.5% underwent mechanical thrombectomy. Surgery was performed in 12.1% patients with haemorrhagic stroke. Rehabilitation was started at hospital in 56% of patients, and 39.6% continued with this treatment at discharge. Mortality was 13.8% at discharge and 25.9% at one year (ischaemic stroke, 25.3%; haemorrhagic stroke, 47.5%); these figures are lower than those previously reported in Guipuzkoa. At one year, 62.5% of patients had a Barthel Index score of 95-100, and 50% a modified Rankin Scale score of 0-2. Conclusions: After the strategic changes implemented in acute stroke care in Guipuzkoa, including the centralisation of the acute stroke care model, mortality rates at discharge and at one year are lower in 2015 than the previously reported rates, with similar rates of independence. These results are consistent with those published by other Spanish and European centres. Resumen: Introducción: En los últimos 15 años se han introducido importantes mejoras en la atención de la enfermedad cerebrovascular aguda (ECVA) en Guipúzcoa que incluyen la implementación de un modelo centralizado en el Hospital Universitario Donostia (HUD), una mejor coordinación entre profesionales, campañas para su detección precoz, nuevos tratamientos, Unidad de Ictus y una rehabilitación específica. El objetivo de este trabajo es describir los resultados de un hospital de referencia (HUD) en un modelo de atención centralizado. Material y métodos: Estudio observacional retrospectivo de una muestra de pacientes dados de alta en el periodo de agosto-diciembre del año 2015 del HUD con diagnóstico de ECVA (CIE-9-MC-430-436 excepto 43310). Revisión de las características basales, atención en fase aguda, y resultados funcionales y de mortalidad al alta y al año. Resultados y Discusión: Se incluyeron 536 pacientes cuya media de edad fue de 73,6 años y cuya comorbilidad era elevada. El ictus isquémico supuso el 64,8% de las altas, seguido de la ECVA hemorrágica (20%) y del accidente isquémico transitorio (AIT) (14,8%). Se atendió en < 6 h a un 53% de pacientes, activándose el “código ictus” en un 37,1%. Un 52,2% ingresaron en la Unidad de Ictus. Un 11,34% de los pacientes con ictus isquémico recibió terapia intravenosa y un 9,5% trombectomia mecánica. Un 12,1% de los pacientes con ECVA hemorrágica fue intervenido quirúrgicamente. El 56% inició rehabilitación en el hospital y un 39,6% la mantuvo al alta. La mortalidad al alta fue de un 13,8% y al año de un 25,9% (ictus isquémico: 25,3% y ECVA hemorrágica: 47,5%), menor a la descrita previamente en Guipúzcoa. Al año un 62,5% de pacientes tenían un Índice de Barthel (IB) 95-100, y un 50% una puntuación en escala de Rankin modificada (mRS) 0-2. Conclusiones: Tras las modificaciones estratégicas introducidas en la atención a la ECVA en Guipúzcoa, incluyendo la centralización del modelo de atención, la mortalidad al alta y anual en 2015 es menor a la descrita previamente, con tasas de autonomía similares. Estos resultados se encuentran en línea con los resultados publicados por parte de otros centros españoles y europeos.